Synthesis of single phase i-AICuFe bulk quasicrystal by spray forming - Srivastava V.C.; Uhlenwinkel V.; Schulz A.; Zoch H.-W.; Mukhopadhyay N.K.; Chowdhury S.G. (My University, 2025)
In the present study, an icosahedral single phase bulk quasicrystalline material based on Al62Cu25.5Fe12.5 has been synthesised by a spray forming route. Microstructural characterization showed an average grain size of 10 urn. The oversprayed fine powder showed the presence of β- and γ- phases, whereas, the deposit consited of the fully single phase bulk quasicrystalline material with compositional homogeneity. The hardness and fracture toughness measurements were carried out at different indentation loads of 50- 500 g. The hardness values varied in the range 10.4-8.1 GPa and fracture toughness was seen to decrease with increasing load. The varionan of hardness with load, which is known as indentation size effect (ISE), has been established clearly. Fracture toughness value was constant in the load range from 200 to 500 g at 1.2 MPa m1/2. The cracking pattern after indentation at higher load has been observed to be intergranular as well as transgranular. The evolution of the single phase bulk quasicrystalline material has been discussed in light of the unique combination of atomization and deposition process elements in spray forming technique.© by Oldenbourg Wissenschaftsverlag.